SIMILE DEVICES IN ALISHER NAVOI'S POETRY (Scientific journal of the Fergana State University, 2022)
This article discusses the composition of the simulators used in Navoighazals. In Navoi's poems, it is reported that simulations are formed using three different grammatical devices and that they have unequal opportunities in the formation of simulators. In Navoi's poetry, examples of extended analogies are given and analyzed, and the importance of the study of analogies in linguistics in general is highlighted.